Exploring seafarers' knowledge, understanding, and proficiency in SEEMP: A strategic training framework for enhancing seafarers' competence in energy-efficient ship operations - Dewan, M. H.; Ahmed Mustafi, M. A.; Matos, F.; Godina, R. (Heliyon, 2024)
With 2.89 % of global carbon emissions caused by human activity, the maritime industry faces an imminent challenge in curbing its carbon footprint despite regulatory initiatives. As the shipping sector expands, the industry faces a projected increase in carbon emissions. Recognizing the key role of seafarers in emission reduction, this article introduces a comprehensive training framework designed to enhance awareness, knowledge, understanding, and skills for implementing energy-efficient ship operations. This study utilizes structural equation modeling to assess the effectiveness of seafarers' training on energy-efficient operation of ships (EEOS) by surveying 144 seafarers across 42 shipping companies worldwide and using structured questionnaires. This study found significant positive correlations between implementing the Ship Energy Efficiency Management Plan (SEEMP) and the training programs initiated by the International Maritime Organization (IMO) and shipping companies. The results of this study indicate that traditional institutional and specialized training programs on EEOS are relatively ineffective for seafarers in implementing SEEMP onboard ships. Furthermore, the study argues that computer and simulator-based training facilitates knowledge, understanding, and proficiency of SEEMP among seafarers more effectively than the onboard training provided by the ship's master and the chief engineer. The proposed training framework emphasizes the importance of initial training using the IMO E-Learning course and IMO "Train the Trainer" programs, followed by shipping companies' in-house training by classification societies, company project teams, and simulator-based training by service providers. The study proposes a strategic training framework that encompasses in-house training conducted by shipping companies in collaboration with partners, simulator-based training provided by specialized training providers, and ongoing onboard training facilitated by the vessel's master and chief engineer, with integration of computer-based training (CBT). This strategic approach intends to improve seafarers' competence in energy-efficient ship operations to meet predetermined carbon intensity targets, which aligns with the broader goal of leading the maritime industry toward a future of net-zero emissions